Compost application boosts soil restoration in highly disturbed hillslope vineyard - Lucchetta, Marco; Romano, Alessandro; Alzate Zuluaga, Monica Yorlady; Fornasier, Flavio; Monterisi, Sonia; Pii, Youry; Marcuzzo, Patrick; Lovat, Lorenzo; Gaiotti, Federica (Frontiers in Plant Science, 2023)
A field trial was carried out to investigate the effects of compost application on a young Cabernet sauvignon vineyard located in a hilly area in the North-East of Italy and subjected to land terracing before plantation. The use of a compost based on manure, pruning residues and pomace at a rate of 65 t ha -1 was compared to the mineral fertilization regime recommended for the vineyards in the area (NPK: 80, 50, 200 kg ha -1 ). A multi-factorial approach that considered soil chemical properties, microbial community structure and function, vine nutritional and vegetative indexes, yield and quality parameters was applied in the attempt of depict interrelated effects of compost on all these factors. Results of this study show that the application of compost for three consequent years greatly increased soil organic matter content and improved the mineral nutrient availability in the soil. Soil biological fertility showed a slow but significant response to compost addition as from the second year of treatment microbial growth and enzyme activity were increased compared to those of the inorganic fertilization, with special regard to enzymes involved in P cycle. A shift in the soil microbial community structure was also observed in compost-treated soil, with higher presence of copiotrophic bacteria, indicators of soil quality, and phosphorus solubilizing bacteria. A decrease of pathogenic fungal strains was also observed. Organic fertilization increased plant nutrient uptake and vegetative growth compared to those observed in chemically fertilized vines. A trend toward increased yield and improvements for some grape quality parameters such as acidity and pH were observed in the first year of production. These results provide evidence that compost can boost soil fertility restoration in vineyard disturbed by land terracing, allowing for agronomic performances comparable or even improved than those of chemically fertilized vines.